Use of Oxalic Acid-Modified Rice Husk for the Adsorption of Neutral Red from Aqueous Solutions - Weihua Zou; Hongjuan Bai; Ke Li; Xiaolan Shi; Runping Han (Adsorption Science & Technology)
Rice husk modified with oxalic acid (MRH) was tested as a lowcost adsorbent for the removal of Neutral Red (NR) dye from aqueous solutions employing batch adsorption procedures. Such studies were conducted by varying various parameters such as the pH, the adsorbent dosage, the salt concentration, the contact time, the concentration of the adsorbate and the temperature. The kinetic experimental data were analyzed using three kinetic equations, viz. the pseudo-first-order equation, the pseudo-second-order equation and the intra-particle diffusion model equation, to examine the mechanism of adsorption and the potential rate-controlling step. The mechanism of the process was found to be complex, consisting of both surface adsorption and pore diffusion. The values of the effective diffusion parameter, D eff , were estimated to be of the order of 10 −8 cm 2 /s, indicated that intra-particle diffusion was not the rate-controlling step. The equilibrium adsorption data obtained at various temperatures were analyzed using the Langmuir, Freundlich and Redlich–Peterson isotherm models using non-linear regressive analysis. The equilibrium adsorption results were better fitted by the Langmuir and Redlich–Peterson isotherms relative to the Freundlich model. Calculated thermodynamic parameters showed that the adsorption of NR onto MRH was feasible, spontaneous and endothermic under the studied conditions. The carboxyl groups on the surface of the modified rice husk (MRH) were primarily responsible for the sorption of NR. It is suggested that MRH may be suitable as an adsorbent material for adsorbing NR from aqueous solutions.